CNSC-24. THE EPILEPTIC LANDSCAPE OF IDH MUTANT GLIOMAS. (14th November 2022) - Drumm, Michael; Wang, Wenxia; Burdett, Kirsten B; Sears, Thomas; Javier, Rodrigo; Cotton, Kristen; Webb, Brynna; Stolz, Jacob; Byrne, Kayla; Unruh, Dusten; Walshon, Jordain; Steffens, Alicia; et al.
Abstract: Tumor-associated epilepsy (TAE) is a frequent complication of diffusely infiltrative gliomas, and impairs quality-of-life. We previously showed that isocitrate dehydrogenase 1 mutant (IDHmut) gliomas were associated with preoperative seizures, and that D2HG increased synchronized bursts in cultured neurons (PMID: 28404805). But the mechanism whereby this occurs, whether IDHmut inhibitors can block this, and whether seizure risk varies by IDHmut status post-operatively, are unknown. We discovered that exogenous 3 mM D2HG had a 150% greater effect on the firing rate of cultured mouse cortical neurons when nonneoplastic glia cells were present versus when they were absent ( P =0.002). Coculture with patient-derived IDHmut glioma cells increased the firing rate of human cortical neuron/astrocyte spheroids by up to 272%, and the IDHmut inhibitor AG881 reduced the excitatory effect of IDHmut glioma cells on spheroids by 79% ( P =0.0008). Using a novel in vivo model of TAE, wherein EEG recordings were taken of immunocompetent mice engrafted with isogenic mouse glioma lines (NRAS/ATRX/TP53mut ± IDHmut), we found that IDHmut gliomas produced 7.6-fold more epileptiform spikes than IDHwt gliomas ( P =0.004). RNA-Seq analysis of the peritumoral mouse brain tissue showed that this increase in spikes was associated with significantly increased expression of key genes known to be upregulated in epilepsy, including SLC12A5, THSB1, VEGFA, FOSL2, and SYNPO . Treatment with 5 mg/kg AG881 by daily oral gavage reduced those spikes in IDHmut-engrafted mice by 51% within three days ( P =0.027), whereas vehicle control had no effect ( P =0.33). Among 247 patients with grade 2–4 adult-type diffuse gliomas, multivariable time-to-event analysis showed that post-operative seizure risk was positively associated with pre-operative seizures, subtotal resection, and IDHmut astrocytoma. Together, these data show that (i) the D2HG product of IDHmut gliomas increases neuronal excitation in a glial-dependent manner; (ii) IDHmut also affects post-operative seizure risk; (iii) IDHmut inhibitors may improve TAE control.